Antimicrobial Stewardship in the Pediatric Emergency Department: An Observational Pre-Post Study - Erika Silvestro; Ilaria Mussinatto; Antonia Versace; Marco Denina; Giulia Pruccoli; Raffaella Marino; Giulia Mazzetti; Lorenzo Scaglione; Federico Vigna; Alessandra Macciotta; Silvia Garazzino; Claudia Bondone (Children)
Background/Objectives: To face antimicrobial resistance, antimicrobial stewardship programs (ASPs) have been implemented in the pediatric age, but the area of urgency remains understudied. We aimed to assess the impact of an educational program on optimizing antibiotic appropriateness in a pediatric ED. Methods: We conducted a pre-post observational study with an audit, intervention, and feedback given to prescribers. We recorded all systemic antibiotic prescriptions for children attending our pediatric ED from January to March and from July to September 2020. The study’s team assigned a score to each prescription, regarding the appropriate molecule, dose, and duration of therapy, according to the diagnosis. From April to June 2020, we held weekly meetings focusing on different pediatric infectious diseases, with interaction between one to three ED physicians and the infectious disease (ID) specialist of the study’s team. We then distributed synthetic digital guidelines adapted to our reality to all prescribers. Results: Optimal antibiotic prescriptions increased after the intervention, with statistical significance (p < 0.001) in four main aspects (overall adequacy: 13% PRE vs. 43% POST; need of antibiotics: 53% vs. 68%; adequacy of the spectrum: 55% vs. 63%; adequacy of the chosen molecule: 54% vs. 62%). We observed an improvement in all the main infectious diseases and concerns all the ED physicians. The prescription of first-choice drugs increased in specific and common illnesses such as otitis and pharyngotonsillitis. Conclusions: An antimicrobial stewardship program is a relevant method for improving the appropriateness of antimicrobial use also in the complex setting of a pediatric ED.